A Review of Therapeutic Herbs (International Journal of Food and Nutritional Sciences, 2022)
Prehistoric people employed medicinal herbs. In emerging nations, medical plant and herbal product preservation, purity, and efficacy are becoming major concerns. Vedas, Quran, and Bible reference herbal treatments and healthcare products extensively. For centuries, medicinal herbs have been used to flavor and preserve food, cure illness, and prevent epidemics. Almost all cultures have prioritized medicinal herbs. Many of the medicines we use today come from plants. Good-for-you herbs have been used for millennia to cure ailments, flavor food, and prevent sickness. The way plants work on a biological level is determined by their secondary metabolites. Plant products regulate microbial development. People have known for a long time that they can help with health problems. Plants have been a great source of natural compounds that are good for human health, especially in the last ten years when natural medicines have been studied in more depth. Herbal treatments for cancer are safe and work well. Chemicals made by a plant's secondary metabolism give it biological abilities that are used all over the world to treat infectious diseases.